Janus plasmonic–magnetic gold–iron oxide nanoparticles as contrast agents for multimodal imaging. Issue 27 (29th June 2017) - Reguera, Javier; Jiménez de Aberasturi, Dorleta; Henriksen-Lacey, Malou; Langer, Judith; Espinosa, Ana; Szczupak, Boguslaw; Wilhelm, Claire; Liz-Marzán, Luis M.
Abstract : Janus Au–Fe3 O4 star-sphere nanoparticles show their high versatility as contrast agents in multimodal imaging. Abstract : The design of compact nanoprobes for multimodal bioimaging is a current challenge and may have a major impact on diagnostics and therapeutics. Multicomponent gold–iron oxide nanoparticles have shown high potential as contrast agents in numerous imaging techniques due to the complementary features of iron oxide and gold nanomaterials. In this paper we describe novel gold–iron oxide Janus magnetic–plasmonic nanoparticles as versatile nanoprobes for multimodal imaging. The nanoparticles are characterized as contrast agents for different imaging techniques, including X-ray computed tomography (CT), T 2 -weighted nuclear magnetic resonance imaging (MRI), photoacoustic imaging (PA), dark-field and bright-field optical microscopy, transmission electron microscopy (TEM), and surface enhanced Raman spectroscopy (SERS). We discuss the effect of particle size and morphology on their performance as contrast agents and show the advantage of a Janus configuration. Additionally, the uptake of nanoparticles by cells can be simultaneously visualized in dark- and bright-field optical microscopy, SERS mapping, and electron microscopy. These complementary techniques allow a complete view of cell uptake in an artifact-free manner, with multiplexing capabilities, and with extra information regarding the nanoparticles' fate inside the cells. Altogether, the results obtained with these non-invasive techniques show the high versatility of these nanoparticles, the advantages of a Janus configuration, and their high potential in multipurpose biomedical applications.